# Mathematics - Trigonometric Identities

Prove:
(tanx)(sinx) / (tanx) + (sinx) = (tanx) - (sinx) / (tanx)(sinx)

What I have so far:

L.S.
= (sinx / cosx) sinx / (sinx / cosx) + sinx
= (sin^2x / cosx) / (sinx + (sinx) (cosx) / cosx)
= (sin^2x / cosx) / (cosx / sinx + sinxcosx)

1. 👍
2. 👎
3. 👁
1. your equation is not an identity the way you wrote it,

try substituting any angle into the equation, it will not satisfy the equation.

The way you wrote it,
LS reduces to simply 2sinx

use brackets to identify the exact order of operation.

1. 👍
2. 👎

## Similar Questions

Which of the following are identities? Check all that apply. (Points : 2) sin2x = 1 - cos2x sin2x - cos2x = 1 tan2x = 1 + sec2x cot2x = csc2x - 1 Question 4. 4. Which of the following equations are identities? Check all that

2. ### Math Trigonometric Identities

1/sinx - sinx = cosx/tanx

3. ### Math (Calculus AB)

For x≠0, the slope of the tangent to y=xcosx equals zero whenever: (a) tanx=-x (b) tanx=1/x (c) sinx=x (d) cosx=x Please help. I have a final tomorrow and I am working diligently to understand every type of problem that may show

4. ### Pre-Calc

How to simplify secx(sinx/tanx)?

1. ### Math

How do I solve this? tan^2x= 2tanxsinx My work so far: tan^2x - 2tanxsinx=0 tanx(tanx - 2sinx)=0 Then the solutions are: TanX=0 and sinX/cosX = 2 sin X Divide through by sinX: we have to check this later to see if allowed (ie sinX

2. ### Trigonometry

Simplify #1: cscx(sin^2x+cos^2xtanx)/sinx+cosx = cscx((1)tanx)/sinx+cosx = cscxtanx/sinx+cosx Is the correct answer cscxtanx/sinx+cosx? Simplify #2: sin2x/1+cos2X = ??? I'm stuck on this one. I don't know what I should do.

3. ### Trig

Verify the identity: tanx(cos2x) = sin2x - tanx Left Side = (sinx/cosx)(2cos^2 x -1) =sinx(2cos^2 x - 1)/cosx Right Side = 2sinx cosx - sinx/cosx =(2sinxcos^2 x - sinx)/cosx =sinx(2cos^2 x -1)/cosx = L.S. Q.E.D.

4. ### precalculus i dont understan this hw

How to prove sec x - tanx sinx= cosx

1. ### TRIG..............

Q.1 Prove the following identities:- (i) tan^3x/1+tan^2x + cot^3x/1+cot^2 = 1-2sin^x cos^x/sinx cosx (ii) (1+cotx+tanx)(sinx-cosx)/sec^3x-cosec^3x = sin^2xcos^2x.

2. ### Maths

If is a n acute angle and tanx=3 4 evaluate cosx-sinx cosx+sinx

3. ### maths - trigonometry

I've asked about this same question before, and someone gave me the way to finish, which I understand to some extent. I need help figuring out what they did in the second step though. How they got to the third step from the

4. ### Trigonometry.

( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! Generally these are done by changing everything to sines and cosines, unless you see some obvious identities. Also generally, it is best to start with the more complicated